Comparison of naturalistic and arbitrary discriminative stimuli during schedule thinning following functional communication training. (30th November 2020) - Boyle, Megan A.; Bacon, McKenzie T.; Carton, Samantha M.; Augustine, John J.; Janota, Taylor A.; Curtis, Kaitlin S.; Forck, Kara L.; Gaskill, Lauren A.
Abstract: We replicated and extended research on incorporating naturalistic discriminative stimuli into schedule thinning following functional communication training with three boys with autism spectrum disorder who engaged in severe behavior. Comparing naturalistic to arbitrary discriminative stimuli, two participants demonstrated differentiated communication in fewer sessions when arbitrary stimuli were used, while the third participant mastered the discriminations in a comparable number of sessions. Although previous research has demonstrated success in rapidly thinning the schedule with arbitrary stimuli, we extended this line of research by evaluating the extent to which differentiated communication would maintain during rapid schedule thinning in both naturalistic and arbitrary conditions. Two participants' communication remained differentiated, and in both conditions, during rapid schedule thinning. However, neither discrimination maintained for the third participant. Results are discussed in terms of the existing literature and directions for future research.